Uji Bilangan Peroksida Pada Minyak Curah Bekas Rumah Tangga Di RT 05 Jalan Kedung Mangu Kecamatan Kenjeran Kota Surabaya - Agnes Yuliana Icha Mauliddia; Rina Rismaya (Fakultas Teknik Universitas Cenderawasih, 2023)
In the past year, the price of bottled oil has soared and its availability has become scarce. So that in its use, people use bulk oil instead of packaged oil and use it repeatedly. Repeated use of cooking oil can increase the value of the peroxide value. Peroxide number value in oil that is not in accordance with SNI 3741-2013 is 10 mek O2/ Kg indicates that the oil is damaged or rancid. This study aims to determine the value of peroxide value in bulk oil that is used repeatedly using the Iodometry method with two experimental repetitions. The results of this study prove that repeated frying can increase the peroxide value significantly. Peroxide number value in sample A1 = 9.82; A2 = 9.416; B1 = 15.95; B2 = 14.455; C1 = 20.41; C2 = 20.904; D1 = 4.969 ; D2 = 5.607 : E1 = 7.001 ; E2 = 7.676. Of the 5 samples tested, it was shown that there were samples B and C whose results exceeded the SNI 3741-2013 Standard, Sample A approached the maximum limit of the SNI 3741-2013 Standard, and Samples D and E were below the SNI 3741-2013 Standard. According to the survey, it was found that samples B and C were the cooking oil samples with the most frequency of frying successively 5 – 7 times. So it can be concluded that the more often the frying is done repeatedly, the higher the peroxide number value in the household used bulk cooking oil.